Early detection of stress in strawberry plants using hyperspectral image analysis - Lowe, Amy (2018)
Strawberry plants produce one of the highest quantities of soft fruits in the UK. The plants are grown in fields and glass houses where the environment is hard to completely control. There are a variety of biotic and abiotic stresses that affect the plants' production rate, lifespan and the quality of the fruit. It is possible to mitigate these stresses, but first they must be detected as early as possible.